Investigating the Strategy of internationalization Architectural Design in Taiwan within the Conceptual Design International Competition - Chang, Chung-Cho; Tai, Shu-Hsien (RSF Conference Series: Business, Management and Social Sciences, 2022)
Internationalization of enterprise is a obvious phenomeno and common strategy for business that want to expand their boundary worldwide. Scholars propose some models that can explain the success well, however, there are no studies on these models applied on the profession of architectural design, even though this profession was internationalized maturely. This study focus on one of the popular mode of architectural competition : Conceptual Design, by the cases in taiwan, and find the Uppsala model is better, followed by the explanatory power of the RBV and OLI.